Numbers, distribution, and ecology of the house sparrow in Lvov (Ukraine) - Bokotey, Andrei A.; Gorban, Igor M. (Zielona Góra: University of Zielona Góra, Institute of Biotechnology & Environmental)
General distribution, numbers, distribution across habitats, food requirements, behaviour, and some other aspects of the biology of House Sparrows Passer domesticus, also their spatio-temporal dynamics in human settlements and larger towns of Ukraine have been poorly known as yet.
Keywords: wróblowe; ornitologia; Ukraina